French, an accommodating language? = Le français, langue d'accueil? - Wright, Sue, 1947- (Current issues in language and society, 2000)
The noted linguist Henriette Walter is a well known media figure in France, who has used her extensive range of scholarly work to take a stance in the current debate on the French language and to debunk the idea that the language is under threat. She shows that French has always been an accommodating language - une langue d'accueil - taking in words from many different sources. This bilingual volume makes Mme Walter's approach accessible to English speakers and provides reactions to it from a number of scholars working in British universities.